Blockade of the Notch1/Jagged1 pathway in Kupffer cells aggravates ischemia-reperfusion injury of orthotopic liver transplantation in mice. (19th May 2019) - Bai, He; Wen, Jian; Gong, Jian-Ping; Wu, Hao; Yuan, Fang-Chao; Cao, Ding; Wu, Ya-Kun; Lai, Xing; Wang, Meng-Hao
Abstract: Liver ischemia-reperfusion injury (IRI) represents a risk factor for early graft dysfunction and an obstacle to expanding donor pool in orthotopic liver transplantation (OLT). Kupffer cells (KCs) are the largest antigen-presenting cell (APC) group and the primary modulators of inflammation in liver tissues. The vital role of Notch1/Jagged1 pathway in mouse OLT model has been reported, however, its potential therapeutic mechanism is unknown. Here, we made use of short hairpin RNA-Jagged1 and AAV-Jagged1 to explore the effects of Notch1/Jagged1 pathway in OLT. In vitro, blockade of Notch1/Jagged1 pathway downregulated the expression of Hairy and enhancer of split-1 ( Hes1 ) gene, which in turn increased the proinflammatory effects of KCs. Moreover, the anti-inflammatory effects of Notch1/Jagged1 pathway were induced by inhibiting Hes1 /gene of phosphate and tension/protein kinase B/Toll-like receptor 4/nuclear factor kappa B ( Hes1 / PTEN /AKT/TLR4/NF-κB) axis in KCs. In vivo, we used a well-established mouse model of OLT to mimic clinical transplantation. Mice were stochastically divided into 6 groups: Sham group (n = 15); Normal saline (NS) group (n = 15); Adeno-associated virus–green fluorescent protein (AAV-GFP) group (n = 15); AAV-Jagged1 group (n = 15); Clodronate liposome (CL) group (n = 15); CL+AAV-Jagged1 group (n = 15) . After OLT the liver damage in AAV-Jagged1 group were significantly accentuated compared to the AAV-GFP group. While blockade of Jagged1 aftet clearence of KCs by CL would not lead to further liver injuries. Taken together, our study demonstrated that blockade of Notch1/Jagged1 pathway aggravates inflammation induced by lipopolysaccharide (LPS) via Hes1 / PTEN /AKT/TLR4/NF-κB in KCs, and the blockade of Notch1/Jagged1 pathway in donor liver increased neutrophil/macrophage infiltration and hepatocellular apoptosis, which suggested the function of Notch1/Jagged1 pathway in mouse OLT and highlighted the protective function of Notch1/Jagged1 pathway in liver transplantation.